2015
DOI: 10.1155/2015/386080
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pressure Changes by Head and Neck Position between High-Volume Low-Pressure and Taper-Shaped Cuffs: A Randomized Controlled Trial

Abstract: The present study compared changes in cuff pressure by head and neck position between high-volume low-pressure (HVLP) and taper-shaped (taper) cuffs in a prospective randomized clinical trial. Methods. Forty patients were intubated using tracheal tubes with either HVLP (n = 20; HVLP group) or taper-shaped (n = 20; Taper group) cuffs. Initial cuff pressure was adjusted to 15, 20, or 25 cmH2O in the neutral position. Cuff pressure was evaluated after changing the head and neck positions to flexion, extension, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 15 publications
3
10
1
2
Order By: Relevance
“…Nevertheless, in our study, the median change in intracuff pressure was minimal-<3 cm H 2 O-and most patients (88%) still demonstrated intracuff pressures of 20-30 cm H 2 O after changing positions. This finding contrasts with that of Komosawa et al, they found that neck flexion and extension caused intracuff pressure to exceed 30 cm H 2 O with high incidences of 90% (flexion) and 50% (extension) [14]. One potential reason for our observations of stable intracuff pressure for the nasotracheal tube could be that nasotracheal tubes move less during posture changes than orotracheal tubes.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…Nevertheless, in our study, the median change in intracuff pressure was minimal-<3 cm H 2 O-and most patients (88%) still demonstrated intracuff pressures of 20-30 cm H 2 O after changing positions. This finding contrasts with that of Komosawa et al, they found that neck flexion and extension caused intracuff pressure to exceed 30 cm H 2 O with high incidences of 90% (flexion) and 50% (extension) [14]. One potential reason for our observations of stable intracuff pressure for the nasotracheal tube could be that nasotracheal tubes move less during posture changes than orotracheal tubes.…”
Section: Discussioncontrasting
confidence: 96%
“…Our novel finding agrees with that of a prior study, intracuff orotracheal tube pressures are affected by head and neck positioning [14,17]. Komosawa et al found that, in adults, head flexion increased the intracuff pressure by a median of 10.3 cm H 2 O, head extension increased the pressure by a median of 5.0 cm H 2 O [14]. Additionally, in pediatric patients, Kako et al noted that neck flexion increased intracuff pressure with the greatest magnitude of mean 6.9 cm H 2 O [17].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations